Role of histone lactylation interference RNA m6A modification and immune microenvironment homeostasis in pulmonary arterial hypertension - Zhao, Shuai-shuai; Liu, Jinlong; Wu, Qi-cai; Zhou, Xue-liang (Frontiers in Cell and Developmental Biology, 2023)
Pulmonary arterial hypertension (PAH) is a severe disease resulting from progressive increases in pulmonary vascular resistance and pulmonary vascular remodeling, ultimately leading to right ventricular failure and even death. Hypoxia, inflammation, immune reactions, and epigenetic modifications all play significant contributory roles in the mechanism of PAH. Increasingly, epigenetic changes and their modifying factors involved in reprogramming through regulation of methylation or the immune microenvironment have been identified. Among them, histone lactylation is a new post-translational modification (PTM), which provides a novel visual angle on the functional mechanism of lactate and provides a promising diagnosis and treatment method for PAH. This review detailed introduces the function of lactate as an important molecule in PAH, and the effects of lactylation on N6-methyladenosine (m6A) and immune cells. It provides a new perspective to further explore the development of lactate regulation of pulmonary hypertension through histone lactylation modification.